Market basket analysis in insurance industry - Marzieh Vahidi Roodpishi; Reza Aghajan Nashtaei (Management Science Letters)
Nowadays, many organizations focus on discovering their customers’ hidden patterns to maintain their competitive position through customer analysis. In fact, more and more organizations are realizing that customers are their most valuable resources. This paper performs a research using data associated with 300 clients of an insurance company in city of Anzali, Iran and they are analyzed using K-Means clustering method. Using demographic variables including gender, age, occupation, education level, marital status, place of residence and clients’ incomes, the study determines the optimal numbers of clusters in order to achieve necessary data for grouping customers. Next, the study uses the method of association rules to find hidden patterns for the insurance industry.